HUBUNGAN ANTARA FREKUENSI DAN JUMLAH PENGGUNAAN COTTON BUD UNTUK TOILET TELINGA TERHADAP KELUHAN TELINGA BERAIR - Rudiansyah, Syafina Dwiayu Ardelia; Qamariah, Nur; Muthmainah, Noor; Rofi’i, Achmad; Kaidah, Siti (Universitas Lambung Mangkurat, 2023)
People often clean their ears with the help of a tool in the form of a cotton bud. The use of cotton buds can result in trauma to the ear canal. Repeated trauma can cause the ear to become inflamed. One complaint of ear inflammation is runny ears. The purpose of this study was to determine the relationship between the frequency and amount of use of cotton buds in the ear toilet for complaints of runny ears. This research is an analytic observational study with a cross sectional approach using Chi Square Fisher Exact Test. The subjects of this study were FK ULM students. The research was conducted using the online Google form, and used a purposive sampling technique. The results of this study showed that the research subjects included in the study population were 245 respondents. The age group that used the most cotton buds is 20 years old (36%). Of the 245 respondents who met the inclusive criteria, there were 96 respondents. The most frequent use of cotton buds was <4 times a week (91.7%). The most amount of cotton buds used was <5 cotton buds per ear toilet (88.5%). The conclusion of this study is that there is a significant relationship between the frequency of using cotton buds and complaints of ear discharge (P value = 0,004). There is no relationship between the amount of use of cotton buds and complaints of ear discharge (P value = 0,43).